Peptide diversity in the venom of the social wasp Polybia paulista (Hymenoptera): A comparison of the intra- and inter-colony compositions - Dias, Nathalia Baptista [UNESP]; Souza, Bibiana Monson de [UNESP]; Gomes, Paulo Cesar [UNESP]; Palma, Mario Sergio [UNESP] (Elsevier B.V., 2014)
The venoms of the social wasps evolved to be used as defensive tools to protect the colonies of these insects against the attacks of predators. Previous studies estimated the presence of a dozen peptide components in the venoms of each species of these insects, which altogether comprise up to 70% of the weight of freeze-dried venoms. In the present study, an optimized experimental protocol is reported that utilizes liquid chromatography coupled to electrospray ionization mass spectrometry for the detection of peptides in the venom of the social wasp Polybia paulista; peptide profiles for both intra- and inter-colonial comparisons were obtained using this protocol. The results of our study revealed a surprisingly high level of intra- and inter-colonial variability for the same wasp species. We detected 78-108 different peptides in the venom of different colonies of P. paulista in the molar mass range from 400 to 3000 Da; among those, only 36 and 44 common peptides were observed in the inter- and intra-colony comparisons, respectively. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Polybia paulista; Venomics; Venom toxin; Peptide toxin; LC/MS